Perancangan Alat Total Dissolved Solid (TDS) Monitoring pada Air Boiler berbasis Mikrokontroler di Pabrik Kelapa Sawit Naga Sakti - Lia Laila (JOURNAL OF APPLIED SCIENCE (JAPPS), 2021)
Steam is a utility that have an essential function in palm oil production. Steam is mainly used in steam turbine to move the generator to produce electricity. Steam also has a lot of other functions such as heating cold oil in storage tank, heating coil in kernel drying, etc. Steam is produced in a machine called boiler. Boiler require a treated feed water as an input. To maintain boiler performance and lifetime, one need to control the TDS (Total Dissolved Solid) in boiler feed water in a range of 2100 2500 ppm. TDS is a parameter that shows the solid concentration which dissolved in the water. TDS has to be checked every hour to maintain its concentration controlled. In a practical use, TDS monitoring is a simple process but take a lot of time to proceed. Water from the sampling pipe collected in a bottle then cooled until room temperature. TDS from cooled boiler water then measured with a device called TDS meter. To control TDS value in the standard condition, the measurement time need to be reduced. Therefore, a faster method to measure TDS in boiler water is needed. An easier and faster measurement using a system which consisted of sensor, microcontroller, LCD display is one of the idea to reduce unneccessary measuring time. The development and experiment of this TDS monitoring device is situated in Nagasakti Palm Oil Mill, Riau Province, Indonesia.